Channel assigning scheme study in LEO constellation communication system combining handover reserving strategy and new call queuing - LI Guang-xia1; LI Su-dan2; FENG Shao-dong1 (Tongxin xuebao)
A channel assigning scheme which was adapted to LEO constellation communication system was proposed. The scheme provided reserved channel for handover call to reduce blocking probability of handoff call.Meanwhile, new call queuing strategy was adopted to restrain new call balockage deterioration caused by reserving scheme. When there was a departure of ongoing call, new call in queue could obtain channel assigning priority-ranked. It is shown that the scheme can reduce the handoff call blocking probability observably, and new call blocking probability is improved at the same time.